2017
DOI: 10.1128/jvi.01976-16
|View full text |Cite
|
Sign up to set email alerts
|

On the Analysis of Intrahost and Interhost Viral Populations: Human Cytomegalovirus as a Case Study of Pitfalls and Expectations

Abstract: Intrahost and interhost assessments of viral diversity are often treated as measures of separate and distinct evolutionary processes, with numerous investigations reporting seemingly incompatible results between the two. For example, in human cytomegalovirus, the nucleotide diversity estimates are 10-fold higher for interhost data, while the number of segregating (i.e., polymorphic) sites is 6-fold lower. These results have been interpreted as demonstrating that sampled intrahost variants are strongly deleteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 25 publications
5
34
0
Order By: Relevance
“…Our identification of shared, minor UCD52 haplotypes between maternal plasma samples, amniotic fluid, placental tissue, and fetal tissues is consistent with previous studies investigating the population genetics of HCMV in newborns [12, 32], which together point towards a loose vertical transmission bottleneck between mother and fetus. While previous studies have estimated transmission bottleneck sizes for HCMV and other viruses, in this study we were unable to quantify transmission bottleneck sizes between mother and fetus due to: 1) low levels of haplotype diversity and 2) haplotype frequencies near the limit of detection.…”
Section: Discussionsupporting
confidence: 90%
“…Our identification of shared, minor UCD52 haplotypes between maternal plasma samples, amniotic fluid, placental tissue, and fetal tissues is consistent with previous studies investigating the population genetics of HCMV in newborns [12, 32], which together point towards a loose vertical transmission bottleneck between mother and fetus. While previous studies have estimated transmission bottleneck sizes for HCMV and other viruses, in this study we were unable to quantify transmission bottleneck sizes between mother and fetus due to: 1) low levels of haplotype diversity and 2) haplotype frequencies near the limit of detection.…”
Section: Discussionsupporting
confidence: 90%
“…This inference has primarily been made within a phylogenetic context, relying on the construction of a single consensus sequence per patient. While such a comparison of consensus sequences can be highly mis-leading when making evolutionary inference (see Renzette et al . 2017), these age-estimates also inherently rely on an accurate knowledge of mutation rates in order to invoke the ‘clock-like’ accumulation of neutral mutations as a proxy for time (Menardo et al .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we here consider the alleles segregating within a population for inference ( i.e., within a patient), whereas previous studies often call a consensus sequence per patient ( i.e., per population) and make inferences based on a collection of such consensus sequences. Such a summary of population-level variation into a single sequence is difficult to interpret, though what is evident is that a great majority of rare alleles will be neglected, and thus only a small subset of total variation ( i.e., common alleles) will be considered (Renzette et al . 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Each isolate was cultured once as part of the diagnostic process with expansion only for the experiments shown here. Although this is a relatively small group of samples due to the constraints discussed previously, it is the largest group of neonatal HSV samples ever compared genotypically or phenotypically, and is similar in size to prior studies of HCMV-infected neonates (25)(26)(27)(28)(29)(30).…”
Section: Neonatal Hsv-2 Samples Represent a Diverse Clinical Populationmentioning
confidence: 99%
“…http://dx.doi.org/10.1101/262055 doi: bioRxiv preprint first posted online Feb. 8, 2018; therapy (23,24). In HTSeq studies of congenital infections by the beta-herpesvirus human cytomegalovirus (HCMV), Renzette et al found evidence for heterogeneous viral populations both within and between hosts (25)(26)(27)(28)(29)(30), which far exceeded the levels of diversity observed in adult HCMV infections (31)(32)(33). Examination of vaccine-associated rashes for varicella zoster virus (VZV; an alpha-herpesvirus) has demonstrated that adult skin vesicles contained a subset of the viral population introduced during vaccination, and found at least 11 VZV genomic loci that were linked to rash formation (34).…”
mentioning
confidence: 99%